Russian roulette [large type] : the inside story of Putin's War on America and the election of Donald Trump - Isikoff, Michael; Corn, David (Twelve, 2018)
"How American democracy was hacked by Moscow to influence the U.S. election and help Donald Trump gain the presidency." -- From book jacket.